PEMANFAATAN POTENSI GAS METANA DI PABRIK KELAPA SAWIT SEI SILAU, PTPN3, SUMATERA UTARA - Irhan Febijanto (Jurnal Teknologi Lingkungan, 2010)
Water waste in Palm Oil Mill (POM) is not effectively utilized yet. Before waste water discharge from POM, the waste water is processed by an aerobic treatment in several ponds to decrease the influence of organic matter. Methane gas generated in the anaerobic ponds is a Green Gas House giving a contribution to global warming impact. In Palm Oil Mill of Sei Silau located in North Sumatera, the potential generated methane gas in two anaerobic ponds has been investigated using measurement of Chemical Oxygen Demand (COD) of waste water in the sites. Based on the potential generated methane gas, the reduction of GHG emission is calculated, and the feasibility of the project as CDM project was evaluated.Keywords : Pabrik Kelapa Sawit, gas metana, gas rumah kaca, proyek CDM (CleanDevelopment Mechanism),, COD (Chemical Oxygen Demand)